Advancements in drug delivery methods for the treatment of brain disease - Partridge, Brittanie; Eardley, Allison; Morales, Brianna E.; Campelo, Sabrina N.; Lorenzo, Melvin F.; Mehta, Jason N.; Kani, Yukitaka; Mora, Josefa K. Garcia; Campbell, Etse-Oghena Y.; Arena, Christopher B.; Platt, Simon; Mintz, Akiva; et al. (Frontiers in Veterinary Science, 2022)
The blood-brain barrier (BBB) presents a formidable obstacle to the effective delivery of systemically administered pharmacological agents to the brain, with 5% of candidate drugs capable of effectively penetrating the BBB. A variety of biomaterials and therapeutic delivery devices have recently been developed that facilitate drug delivery to the brain. These technologies have addressed many of the limitations imposed by the BBB by: 1) designing or modifying the physiochemical properties of therapeutic compounds to allow for transport across the BBB; 2) bypassing the BBB by administration of drugs via alternative routes; and 3) transiently disrupting the BBB (BBBD) using biophysical therapies. Here we specifically review colloidal drug carrier delivery systems, intranasal, intrathecal, and direct interstitial drug delivery methods, focused ultrasound BBBD, and pulsed electrical field induced BBBD, as well as the key features of BBB structure and function that are the mechanistic targets of these approaches. Each of these drug delivery technologies are illustrated in the context of their potential clinical applications and limitations in companion animals with naturally occurring intracranial diseases.